La fábula invertida o sobre la amoralidad de la fábula —a propósito de la fábula como herramienta de interpretación antropológica— (2021)
Usually the fable is understood as that literary genre in which there are characters (mainly animals) who, not being humans, behave as if they were, however; in this paper we will try to show it is possible that in such stories the animals are not the ones humanized, but the human is the one who is bestialized, and that this perspective will enable us to understand the fable as an anthropological interpretation tool.